2017
DOI: 10.1161/circoutcomes.116.003186
|View full text |Cite|
|
Sign up to set email alerts
|

Total Center Percutaneous Coronary Intervention Volume and 30-Day Mortality

Abstract: T he relationship between procedural volume and patient outcomes is an important consideration in the provision of percutaneous coronary intervention (PCI). Studies that have suggested the existence of a relationship have informed international guidelines 1-3 on the minimum procedural limits recommended for annual center volume to ensure safe and effective patient care. This is also reflected in recent UK guidance on the provision of PCI. 4 For acute myocardial infarction, the establishment of high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Although evidence suggests institutional PCI volumes are not associated with clinical outcomes,30 our finding that PPCI performed by operators performing <55 PPCI per year is associated with significantly higher probability of 30-day mortality compared with high-volume operators, should prompt re-examination of the AHA recommendation that ≥11 PPCI per year per operator is an acceptable operator volume for the provision of PPCI 20…”
Section: Discussionmentioning
confidence: 72%
“…Although evidence suggests institutional PCI volumes are not associated with clinical outcomes,30 our finding that PPCI performed by operators performing <55 PPCI per year is associated with significantly higher probability of 30-day mortality compared with high-volume operators, should prompt re-examination of the AHA recommendation that ≥11 PPCI per year per operator is an acceptable operator volume for the provision of PPCI 20…”
Section: Discussionmentioning
confidence: 72%
“…So, the number of teeth within a patient may not be independent of the disease status. In studies investigating the association between the volume of procedures carried out per surgeon, the performance of surgeons performing a specific operation assessed by the proportion of successful operations, may be associated with the number of operations performed [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that observational research into the relationship between patient survival outcomes and centre volume in the UK has not found that lower volume centres were putting patients at risk. 1,2…”
Section: Number Of Cases Per Hospitalmentioning
confidence: 99%